Liquid composition and method for producing same

A liquid composition with tetrafluoroethylene and hydrocarbon polymers, using specific dispersion media ratios, addresses surfactant residue issues, enhancing dispersion stability and surface properties in molded articles for printed circuit boards.

JP7615727B2Active Publication Date: 2025-01-17AGC INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021019971
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-12
Filing Date
2021-02-10
Publication Date
2025-01-17
Estimated Expiration
2041-02-10

AI Technical Summary

Technical Problem

Existing liquid compositions containing tetrafluoroethylene polymers for dielectric layers in printed circuit boards often suffer from surfactant residues affecting surface properties and adhesion, leading to issues with wettability and smoothness.

Method used

A liquid composition comprising tetrafluoroethylene polymer, hydrocarbon polymer, non-polar and polar liquid dispersion media, with specific mass ratios, which enhances dispersion stability and adhesion, forming molded articles with excellent surface and electrical properties.

Benefits of technology

The composition achieves improved dispersion stability, surface smoothness, and electrical properties in molded articles, particularly in sheet materials used as adhesive layers or coverlay films for printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615727000001
    Figure 0007615727000001
  • Figure 0007615727000002
    Figure 0007615727000002
Patent Text Reader

Abstract

To provide a liquid composition that can form a layer (adhesive layer) having adhesion properties and electric characteristics and contains a hydrocarbon polymer, and a sheet material having a layer that has adhesion properties and electric characteristics.SOLUTION: A liquid composition has powder of a tetrafluoroethylene polymer, a hydrocarbon polymer, a nonpolar liquid dispersion medium, and a polar liquid dispersion medium. The mass ratio of the content of the polar liquid dispersion medium to the content of the nonpolar liquid dispersion medium is 20 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid composition comprising a powder containing a tetrafluoroethylene-based polymer, a hydrocarbon-based polymer, and a specific liquid dispersion medium, a method for producing such a liquid composition, and a sheet material formed from such a liquid composition. [Background technology]

[0002] Tetrafluoroethylene polymers such as polytetrafluoroethylene (PTFE) have excellent physical properties such as chemical resistance, water and oil repellency, heat resistance, and electrical properties, and are known to be used in a variety of forms and for a variety of applications, such as powders, dispersions, and films. In recent years, signals have become increasingly high frequency, and there is a demand for materials with electrical properties such as low dielectric constant and low dielectric loss tangent, and excellent insulating performance. In response to this, liquid compositions containing tetrafluoroethylene polymer powder have attracted attention as materials for forming dielectric layers of printed circuit boards that have excellent electrical properties such as low dielectric constant and low dielectric loss tangent and are compatible with high frequencies.

[0003] In order to improve the adhesion of tetrafluoroethylene polymers to other materials and obtain materials with excellent insulating performance, various proposals have been made regarding liquid compositions. Patent Document 1 discloses a thermosetting liquid composition containing the above powder, rubber particles, silica filler, epoxy resin, and a curing agent from the viewpoint of improving the substrate adhesion and the thickness uniformity of the dielectric layer when the dielectric layer is formed. Patent Document 2 discloses a liquid composition containing the above powder and a thermoplastic elastomer from the viewpoint of improving the viscosity, storage stability, and mixability with other resin materials of the liquid composition. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-35059 A [Patent Document 2] JP 2017-222762 A Summary of the Invention [Problem to be solved by the invention]

[0005] The liquid compositions described in Patent Documents 1 and 2 contain a surfactant as a constituent from the viewpoint of dispersion stability. When the liquid composition contains a surfactant, particularly a fluorine-based surfactant, there is a problem that the surfactant remains in a molded product obtained from the liquid composition and affects the surface properties (wettability, smoothness, etc.).

[0006] As a result of intensive research, the present inventors have found that a liquid composition containing a tetrafluoroethylene polymer, a hydrocarbon polymer, and a specific type of liquid dispersion medium, the content ratio of which is within a specific range, can form a molded product having excellent dispersion stability and excellent surface physical properties. In addition, they have found that such a molded product has particularly excellent adhesiveness and electrical properties. An object of the present invention is to provide a liquid composition having excellent dispersion stability, a method for producing such a liquid composition, and a molded product, typically a sheet material, formed from such a liquid composition. [Means for solving the problem]

[0007] The present invention has the following aspects. <1> A liquid composition comprising a tetrafluoroethylene-based polymer powder, a hydrocarbon-based polymer, a non-polar liquid dispersion medium, and a polar liquid dispersion medium, wherein the mass ratio of the content of the polar liquid dispersion medium to the content of the non-polar liquid dispersion medium is 20 or less. <2> The non-polar liquid dispersion medium is an aromatic hydrocarbon. <1> A liquid composition comprising: <3> The polar liquid dispersion medium is at least one selected from alcohols, ketones, esters and amides. <1> or <2> A liquid composition comprising: <4> The hydrocarbon-based polymer is a styrene-based polymer or an olefin-based polymer; <1> ~ <3> Any of the liquid compositions. <5> The hydrocarbon-based polymer is a styrene-conjugated diene block copolymer; <1> ~ <4> Any of the liquid compositions. <6> The hydrocarbon-based polymer has a polar group. <1> ~ <5> Any of the liquid compositions. <7> The content of the hydrocarbon-based polymer is greater than the content of the tetrafluoroethylene-based polymer. <1> ~ <6> Any of the liquid compositions. <8> The tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing a unit based on perfluoro(alkyl vinyl ether) or a unit based on hexafluoropropene, or a polytetrafluoroethylene having a number average molecular weight of 200,000 or less. <1> ~ <7> Any of the liquid compositions. <9> The content of the tetrafluoroethylene-based polymer powder is 5% by mass or more based on the total mass of the liquid composition. <1> ~ <8> Any of the liquid compositions. <10> does not contain any fluorine-containing compound other than the tetrafluoroethylene-based polymer; <1> ~ <9> Any of the liquid compositions. <11> kneading a composition containing the tetrafluoroethylene-based polymer powder, the hydrocarbon-based polymer, and the non-polar liquid dispersion medium or the polar liquid dispersion medium to obtain a kneaded mixture, and mixing the kneaded mixture with the non-polar liquid dispersion medium or the polar liquid dispersion medium to obtain the liquid composition. <1> ~ <10> A method for producing any one of the liquid compositions described above. <12> The kneaded product is a kneaded paste or a kneaded powder. <11> Manufacturing method. <13> <1> ~ <9> A sheet material formed from any one of the liquid compositions above. <14> An adhesive sheet used as an adhesive layer between substrates. <13> Sheet material. <15> It is a coverlay film that is attached to a printed wiring board so as to cover the metal wiring. <13> Sheet material. Effect of the Invention

[0008] According to the present invention, there are provided a liquid composition having excellent dispersion stability, a method for producing such a liquid composition, and a molded product, typically a sheet material, formed from such a liquid composition. The sheet material formed from the liquid composition of the present invention has excellent surface properties, typically wettability and smoothness, and excellent electrical properties, and is useful, for example, as an adhesive sheet used as an adhesive layer between substrates, or a coverlay film to be adhered to a printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following terms have the following meanings. "D50" is the cumulative 50% diameter on a volume basis of a powder determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, the total volume of the particle group is set to 100%, and a cumulative curve is calculated. D50 is the particle diameter at the point on the cumulative curve where the cumulative volume is 50%. "D90" is the cumulative volume particle size of the powder, and is the volume-based cumulative 90% diameter of the powder, which is calculated in the same manner as "D50". D50 and D90 are determined by dispersing the powder in water and analyzing it by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). The "specific surface area" is a value calculated by measuring a powder using a gas adsorption (constant volume method) BET multipoint method, and is determined using a NOVA4200e (manufactured by Quantachrome Instruments). The "melting temperature of a polymer" is the temperature corresponding to the maximum of the melting peak as measured by differential scanning calorimetry (DSC). The "melt viscosity of polymer" is a value measured in accordance with ASTM D 1238 using a flow tester and a 2Φ-8L die, with a polymer sample (2 g) that had been heated at the measurement temperature in advance for 5 minutes being held at the measurement temperature under a load of 0.7 MPa. The "viscosity of the liquid composition" is the viscosity measured using a Brookfield viscometer at 25° C. and 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is used. "Thixotropy ratio" refers to the viscosity η of a liquid composition measured at a rotation speed of 30 rpm. 1 The viscosity η measured at a rotation speed of 60 rpm 2 Each viscosity measurement is repeated three times, and the average of the three measured values ​​is used. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."

[0010] The liquid composition of the present invention (hereinafter also referred to as "the composition") contains a powder (hereinafter also referred to as "F powder") of a tetrafluoroethylene polymer (hereinafter also referred to as "F polymer"), a hydrocarbon polymer, a non-polar liquid dispersion medium (hereinafter also referred to as "dispersion medium A"), and a polar liquid dispersion medium (hereinafter also referred to as "dispersion medium B"), and the mass ratio of the content of dispersion medium B to the content of dispersion medium A (hereinafter also referred to as "B / A") is 20 or less. The composition is a liquid composition in which the F powder is dispersed and the hydrocarbon polymer is highly dissolved and dispersed.

[0011] This composition has excellent dispersion stability and can form a molded product with excellent surface properties and electrical properties. Although the mechanism of action is unclear, it is generally estimated as follows. This composition contains dispersion medium A and dispersion medium B, and at least a part of the hydrocarbon polymer can be dissolved in dispersion medium A. On the other hand, F powder can be well dispersed in dispersion medium B. Furthermore, in this composition in which these dispersion media are present at a specific mass ratio, the properties are balanced, and the dissolved hydrocarbon polymer acts as a dispersant, thickener, and thixotropy imparting agent to improve the dispersion stability of F powder and improve the liquid properties of the entire liquid composition. In addition, the hydrocarbon polymer exerts an effect of lowering the surface tension of the liquid composition, and is also thought to improve the leveling properties when forming a molded product from the liquid composition. Furthermore, since the hydrocarbon polymer itself has electrical properties with a low dielectric tangent, it also contributes to improving the electrical properties of the molded product formed from the liquid composition. As a result, it is believed that a molded article having excellent surface properties, such as wettability and smoothness, and excellent electrical properties can be formed from this composition.

[0012] The D50 of the F powder in the present invention is preferably 20 μm or less, more preferably 8 μm or less. The D50 of the F powder is preferably 0.01 μm or more, more preferably 0.1 μm or more. Also, the D90 of the F powder is preferably 10 μm or less. In this range of D50 and D90, the flowability and dispersibility of the F powder become good, and the electrical properties (low dielectric constant, etc.) and heat resistance are most easily exhibited.

[0013] In this composition, from the viewpoint of dispersion stability, the bulk density of F powder is 0.15 g / m 2 More than 0.20 g / m is preferable. 2 More preferably, the bulk density of F powder is 0.50 g / m 2 Less than 0.35 g / m is preferred. 2 The following is more preferred:

[0014] The F powder in the present invention may contain a resin other than the F polymer or an inorganic filler, but preferably contains the F polymer as the main component. The content of the F polymer in the F powder is preferably 80% by mass or more, more preferably 100% by mass. Examples of the resin include heat-resistant resins such as aromatic polyester, polyamideimide, (thermoplastic) polyimide, polyphenylene ether, polyphenylene oxide, and maleimide. Examples of the inorganic filler include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, and the like), boron nitride, and magnesium metasilicate (steatite). At least a part of the surface of the inorganic filler may be surface-treated.

[0015] The F powder containing a resin other than the F polymer or an inorganic filler may have a core-shell structure having an F polymer as the core and a resin other than the F polymer or an inorganic filler as the shell, or may have a core-shell structure having an F polymer as the shell and a resin other than the F polymer or an inorganic filler as the core. Such an F powder can be obtained, for example, by coalescing (collision, aggregation, etc.) a powder of an F polymer and a powder of a resin other than the F polymer or an inorganic filler.

[0016] The F polymer in the present invention is a polymer containing units (TFE units) based on tetrafluoroethylene (TFE). The F polymer is preferably heat-meltable. The melting temperature of the F polymer is preferably 280 to 325°C, more preferably 300 to 325°C. In such a case, the molded article formed from the composition tends to have excellent heat resistance. The glass transition point of the F polymer is preferably 75 to 125°C, more preferably 80 to 100°C.

[0017] Examples of F polymers include polytetrafluoroethylene (PTFE), polymers containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), and polymers containing units based on hexafluoropropene (HFP) (FEP), with PFA being preferred. PAVE includes CF 2 =CFOCF 3 , C.F. 2 =CFOCF 2 CF 3 and CF 2 =CFOCF 2 CF 2 CF 3 (PPVE) is preferred, with PPVE being more preferred.

[0018] The F polymer preferably has a polar functional group. The polar functional group may be contained in a unit in the F polymer, or may be contained in a terminal group of the main chain of the polymer. Examples of the latter embodiment include an F polymer having a polar functional group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer having a polar functional group obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. The polar functional group is preferably a hydroxyl group-containing group or a carbonyl group-containing group, and from the viewpoint of the dispersion stability of the present composition, a carbonyl group-containing group is more preferable. The hydroxyl group-containing group is preferably a group containing an alcoholic hydroxyl group, and is preferably -CF 2 CH 2 OH or -C(CF 3 ) 2 OH is more preferred. The carbonyl-containing group is a group that contains a carbonyl group (>C(O)), and includes a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH 2 ), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)- etc.) or a carbonate group (-OC(O)O-), and an acid anhydride residue is more preferred.

[0019] When the F polymer has a carbonyl group-containing group, the number of carbonyl group-containing groups in the F polymer is 1×10 6The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000, and further preferably 800 to 1500. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.

[0020] The F polymer is preferably a polymer (1) having a polar functional group containing TFE units and PAVE units, or a polymer (2) having no polar functional group containing TFE units and PAVE units and containing 2.0 to 5.0 mol % of PAVE units based on all units. These F polymers not only have excellent dispersion stability in powder form, but also tend to distribute more densely and homogeneously in molded products (polymer layers, etc.) formed from the present composition. Furthermore, they tend to form microspherulites in the molded products, which tends to increase adhesion with other components. As a result, molded products with excellent surface smoothness, adhesion, and electrical properties are more likely to be obtained.

[0021] The polymer (1) is preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a polar functional group, and more preferably a polymer containing these units in the amounts, in this order, of 90 to 99 mol %, 0.5 to 9.97 mol %, and 0.01 to 3 mol %, based on all units. Moreover, the monomer having a polar functional group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"). Specific examples of polymer (1) include the polymers described in WO 2018 / 16644.

[0022] Polymer (2) is composed of only TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol% of TFE units and 2.0 to 5.0 mol% of PAVE units based on all units. The content of PAVE units in polymer (2) is preferably 2.1 mol% or more, more preferably 2.2 mol% or more, based on all units. In addition, the polymer (2) having no polar functional group means that the number of carbon atoms constituting the polymer main chain is 1×106 This means that the number of polar functional groups in the polymer is less than 500 per unit. The number of the polar functional groups is preferably 100 or less, more preferably less than 50. The lower limit of the number of the polar functional groups is usually 0. The polymer (2) may be produced by using a polymerization initiator or a chain transfer agent that does not generate a polar functional group as a terminal group of the polymer chain, or by fluorinating an F polymer having a polar functional group (such as an F polymer having a polar functional group derived from a polymerization initiator at the terminal group of the main chain of the polymer). As a method of fluorination treatment, a method using fluorine gas (see JP 2019-194314 A, etc.) can be mentioned.

[0023] As the F polymer, PTFE having a number average molecular weight (Mn) of 200,000 or less (low molecular weight PTFE) is more preferable. In this case, a molded product formed from this molded product is likely to have excellent electrical properties such as a low dielectric tangent. The number average molecular weight (Mn) of PTFE is calculated based on the following formula (1). Mn = 2.1 × 10 10 ×ΔHc -5.16 ... (1) In formula (1), ΔHc represents the heat of crystallization (cal / g) of PTFE measured by differential scanning calorimetry. The Mn of the low molecular weight PTFE is preferably 100,000 or less, more preferably 50,000 or less. The Mn of the low molecular weight PTFE is preferably 10,000 or more.

[0024] The hydrocarbon polymer in the present invention is preferably a styrene-based polymer or an olefin-based polymer. Examples of the styrene-based polymer include homopolymers of styrene, and copolymers of styrene and conjugated dienes or (meth)acrylic esters (styrene-butadiene rubber, styrene-based core-shell type copolymers, styrene-based block copolymers, etc.). Among these, styrene-based elastomers are preferred because they have the properties of both rubber and plastic and become plasticized and flexible when heated.

[0025] Examples of such styrene-based elastomers include block copolymers having a polystyrene block as a hard segment and a polyolefin block as a soft segment, and styrene-conjugated diene block copolymers are preferred, and diblock or triblock copolymers are preferred. The styrene-conjugated diene block copolymer is preferably hydrogenated. In this case, the above-mentioned mechanism of action is easily enhanced. Specific examples of styrene-based polymers include SBS (polystyrene-polybutadiene-polystyrene block copolymer), SEP (polystyrene-poly(ethylene / propylene) block copolymer), SEPS (polystyrene-poly(ethylene / propylene)-polystyrene block copolymer), SEBS (polystyrene-poly(ethylene / butylene)-polystyrene block copolymer), SEEPS (polystyrene-poly(ethylene-ethylene / propylene)-polystyrene block copolymer), and SIS (polystyrene-polyisoprene-polystyrene block copolymer). These have low dielectric tangents and excellent heat resistance, and are easily dispersed or dissolved in the composition. Examples of styrene-based elastomers that are industrially produced and available include Tuftec (registered trademark) from Asahi Kasei Corporation, the SIS series and TR series and DYNARON (registered trademark) from JSR Corporation, Septon (registered trademark) from Kuraray Co., Ltd., and Kraton G Polymer from Kraton Polymers.

[0026] Examples of olefin-based polymers include polymers of unsaturated aliphatic hydrocarbons such as ethylene, propylene, butene, hexene, octene, butadiene, isoprene, cyclopentadiene, and ethylidene norbornene, and preferably include polymers having rubber elasticity. Examples of olefin-based polymers having rubber elasticity include ethylene-propylene rubber (EPM), polybutadiene, butyl rubber (isobutylene / isoprene-based polymer), polyisoprene, ethylene-propylene-diene rubber (EPDM), and ethylene-1-octene copolymer. Among them, olefin-based elastomers that have the properties of both rubber and plastic and can be easily molded by plasticizing with heat are preferred.

[0027] Olefin elastomers have polyolefins such as polyethylene and polypropylene as hard segments and rubber components such as EPM and EPDM as soft segments. They can be broadly divided into three types: blends of polyolefins and rubber components, dynamic crosslinking types, and polymerization types. Examples of industrially produced and available olefin-based elastomers include THERMORUN (registered trademark) and TREXPRENE (registered trademark) from Mitsubishi Chemical Corporation, the RB series and EXCELINK (registered trademark) from JSR Corporation, the ESPOLEX (registered trademark) TPE series from Sumitomo Chemical Co., Ltd., and ENGAGE (registered trademark) from Dow.

[0028] The hydrocarbon-based polymer in the present invention, preferably a styrene-based polymer or an olefin-based polymer, preferably has a polar group from the viewpoint of further improving the adhesion with the F polymer or the inorganic filler described later. Examples of such polar groups include an epoxy group, a carbonyl group-containing group, a hydroxyl group-containing group, an isocyanate group, and an amino group. The hydrocarbon-based polymer having such a polar group is industrially produced, and a commercially available product that is easily available can be used.

[0029] The glass transition temperature of the hydrocarbon polymer is preferably 10° C. or lower, more preferably 5° C. or lower. If the glass transition temperature is 10° C. or lower, the rubber elasticity is improved, and the foldability of a molded product, typically a sheet material, formed from the composition is further improved. In addition, it is preferable that at least a part of the hydrocarbon polymer is soluble in the dispersion medium A.

[0030] The number average molecular weight of the hydrocarbon polymer is preferably in the range of 30,000 to 400,000. From the viewpoint of enhancing the above-mentioned mechanism of action, the content of the hydrocarbon-based polymer is preferably greater than the mass content of the F polymer, and is preferably at least twice the mass content of the F polymer. The content of the hydrocarbon-based polymer is preferably 10 times or less, and more preferably 5 times or less, the mass content of the F polymer.

[0031] The dispersion medium A in the present composition is a compound that is liquid at 25°C under atmospheric pressure and is classified as non-polar, and is preferably an aliphatic hydrocarbon or an aromatic hydrocarbon, more preferably an aromatic hydrocarbon. The non-polar dispersion medium is preferably a dispersion medium having a Rohrschneider polarity parameter of 3.0 or less. The boiling point of the dispersion medium A is preferably in the range of 30 to 200°C. Two or more types of dispersion medium A may be used in combination.

[0032] Examples of the aliphatic hydrocarbon include pentane, hexane, heptane, octane, nonane, decane, dodecane, cyclopentane, cyclohexane, methylcyclohexane, ethylcyclohexane, cyclooctane, cyclodecane, cyclododecane, liquid paraffin, limonene, dipentene, and myrcene. Examples of aromatic hydrocarbons include benzene, toluene, xylene, ethylbenzene, styrene, cumene, mesitylene (1,3,5-trimethylbenzene), cymene, diethylbenzene, and naphthalene, with toluene or xylene being more preferred.

[0033] The dispersion medium B in the present invention is a compound that is liquid at 25°C under atmospheric pressure and is classified as polar, and is preferably at least one polar compound selected from alcohols, ketones, esters, and amides, and is more preferably a ketone. The polar dispersion medium is preferably a dispersion medium having a Rohrschneider polarity parameter of 4.0 or more. The boiling point of the dispersion medium B is preferably in the range of 30 to 200°C. Two or more types of dispersion medium B may be used in combination.

[0034] Examples of the alcohol include methanol, ethanol, n-propanol, isopropanol, butanol, pentanol, hexanol, cyclohexanol, ethylene glycol, propylene glycol, butanediol, neopentyl glycol, methylpentanediol, diethylene glycol, dipropylene glycol, and glycerin. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Examples of esters include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, γ-valerolactone, ethylene glycol monoacetate, ethylene glycol monomethyl ether acetate, diethylene glycol monoacetate, propylene glycol monoacetate, propylene glycol diacetate, propylene glycol monomethyl ether acetate, and dipropylene glycol monoacetate. Examples of the amide include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone, and N-methyl-2-pyrrolidone, N,N-dimethylformamide, or N,N-dimethylacetamide is preferred.

[0035] In the present composition, the mass ratio (B / A) of the content of dispersion medium B to the content of dispersion medium A is not more than 20. B / A is preferably not more than 15, more preferably not more than 10, and even more preferably not more than 1, while it is preferably not less than 0.1, and more preferably not less than 0.2. When B / A is within this range, the above-mentioned mechanism of action is enhanced, the present composition has excellent dispersion stability, and the formed molded product, typically a sheet material, has even better electrical properties and surface smoothness.

[0036] The composition may also include other materials. The present composition preferably further contains an epoxy resin from the viewpoint of improving the adhesion and hardness of a molded product such as a sheet material formed from the composition. Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, and tetraphenylethane type epoxy resins. Two or more of these epoxy resins may be used in combination. The epoxy resin may be either a liquid epoxy resin at 20°C or a solid epoxy resin at 20°C.

[0037] When the composition further contains an epoxy resin, the content of the epoxy resin is, from the viewpoint of obtaining an insulating layer exhibiting good mechanical strength and insulating reliability, preferably 1 mass % or more, and more preferably 5 mass % or more, relative to the mass of the non-volatile components in the composition, and is preferably 40 mass % or less, and more preferably 20 mass % or less.

[0038] When the composition further contains an epoxy resin, the composition preferably contains a curing agent, which is an agent for curing the epoxy resin, and specific examples of the curing agent include active ester curing agents, phenolic curing agents, naphthol curing agents, benzoxazine curing agents, cyanate ester curing agents, and carbodiimide curing agents.

[0039] The present composition may further contain an inorganic filler from the viewpoint of improving the physical properties (low expansion, UV absorption, electrical properties, etc.) of the molded product obtained therefrom. When the present composition contains an inorganic filler, from the above viewpoints, the content thereof is preferably 1% by mass or more, more preferably 5% by mass or more, and on the other hand, preferably 40% by mass or less, more preferably 25% by mass or less, based on the mass of the non-volatile components in the present composition.

[0040] The inorganic filler is preferably a nitride filler or an inorganic oxide filler, and more preferably a boron nitride filler, a beryllia filler (a beryllium oxide filler), a silicate filler (a silica filler, a wollastonite filler, a talc filler), or a metal oxide filler (cerium oxide, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, etc.). Such an inorganic filler is easy to balance the interactions between the components and is easy to further improve the dispersion stability of the present composition. In addition, the physical properties are easily manifested remarkably in the molded product. Among them, the inorganic filler preferably contains silica. The content of silica in the inorganic filler is preferably 50% by mass or more, more preferably 75% by mass. The content of silica is preferably 100% by mass or less, more preferably 90% by mass or less.

[0041] The inorganic filler is preferably surface-treated. Examples of the surface treatment agent used for such surface treatment include polyhydric alcohols (trimethylolethane, pentaerythritol, propylene glycol, etc.), saturated fatty acids (stearic acid, lauric acid, etc.), esters thereof, alkanolamines, amines (trimethylamine, triethylamine, etc.), paraffin wax, silane coupling agents, silicones, and polysiloxanes. The silane coupling agent is preferably 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane or 3-isocyanatopropyltriethoxysilane.

[0042] The average particle size of the inorganic filler is preferably 1 μm or less, more preferably 0.8 μm or less, and even more preferably 0.6 μm or less.The average particle size is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.01 μm or more. Specific examples of inorganic fillers include silica fillers (such as the "Admafine" series manufactured by Admatechs Co., Ltd.), zinc oxide surface-treated with esters such as propylene glycol dicaprylate (such as the "FINEX" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica (such as the "SFP" series manufactured by Denka Co., Ltd.), coated with polyhydric alcohols and inorganic substances (such as the "Tipaque" series manufactured by Ishihara Sangyo Kaisha, Ltd.), and rutile-type titanium dioxide surface-treated with alkylsilanes (such as the "JMT" series manufactured by Teika Corporation).

[0043] The shape of the inorganic filler may be any of granular, needle-like (fibrous) and plate-like. Specific shapes of the inorganic filler include spherical, scale-like, layered, leaf-like, apricot kernel-like, columnar, cockscomb-like, equiaxial, leaf-like, micaceous, block-like, flat, wedge-like, rosette-like, net-like and prismatic shapes. In addition, the inorganic filler is preferably hollow. The average particle size (D50) of the hollow inorganic filler is preferably 0.01 μm or more, more preferably 0.1 μm or more. The average particle size is more preferably 10 μm or less, even more preferably 5 μm or less. In such a case, in a molded product molded from the composition, the inorganic fillers are likely to be filled in contact with each other, and the molded product is likely to have excellent electrical insulation properties. The specific surface area of ​​inorganic filler (BET method) is 10 to 250 m 2 / g is preferable, and 40 to 100m 2 / g is more preferred.

[0044] The average pore size of the hollow inorganic filler is preferably 10 to 1000 nm, more preferably 50 to 100 nm. The average pore size is determined by directly observing a plurality of pores (100 pores) using a scanning electron microscope (SEM) or the like, and the average value is taken as the average pore size. In the case of irregular pores, the maximum diameter of the pores is taken as the pore size. The apparent specific gravity of the hollow inorganic filler is preferably 100 g / L or less, more preferably 30 to 60 g / L, in order to sufficiently increase the porosity. The apparent specific gravity of the hollow inorganic filler is determined from the mass and volume of the inorganic filler placed in a measuring cylinder (capacity 250 mL). The bulk density of the hollow inorganic filler is 5 g / cm 3 Less than 1g / cm is preferable. 3 The lower limit of the bulk density is preferably 0.1 or more. The hollow inorganic filler is preferably a hollow silica filler. A specific example of the hollow silica filler is the hydrophobic AEROSIL series "RX200" (manufactured by Nippon Aerosil Co., Ltd.).

[0045] The present composition may further contain various dispersants and surfactants that are added to conventionally proposed liquid dispersions containing F polymer powder in order to impart dispersibility, such as a fluorine-based surfactant having a hydroxyl group or an oxyalkylene group as a hydrophilic portion and a fluorine-containing organic group (such as a perfluoroalkyl group) as a hydrophobic portion. However, since the composition contains dispersion medium A and dispersion medium B in a specific mass ratio (B / A), the hydrocarbon polymer acts as a dispersant, thickener, and thixotropy imparting agent as described in the above-mentioned mechanism of action, and is considered to improve the dispersion stability and liquid properties of the F powder in the composition, so that it does not necessarily need to contain a dispersant or surfactant. In particular, from the viewpoint of maintaining the adhesiveness of the sheet material formed from the composition and handling of the sheet material, which will be described later, it is preferable that the composition does not contain a fluorine-containing compound other than the F polymer.

[0046] The content of the F powder in the present composition is preferably 5 to 40% by mass based on the total mass of the present composition. The content of the hydrocarbon polymer in the present composition is preferably 5 to 4 mass % or more based on the total mass of the present composition. The ratio of the mass of the hydrocarbon polymer to the mass of the F powder in the present composition is preferably 0.5-10, and more preferably 1-5. When the content of F powder, the content of the hydrocarbon polymer, or the ratio is within the above range, the composition tends to have excellent dispersion stability due to the above-mentioned mechanism of action.

[0047] The viscosity of the composition is more preferably 75 to 1000 mPa·s, and even more preferably 100 to 500 mPa·s, in which case the composition has excellent dispersion stability, as well as excellent coatability and mixability with varnishes of different polymers. The thixotropy ratio of the present composition is preferably 1.0 to 2.2, more preferably 1.5 to 2.0. In this case, the present composition has excellent dispersion stability and good coatability, and the homogeneity of the formed molded product is easily improved. In addition, the present composition has improved mixability with varnishes of different polymers. Due to the above-mentioned mechanism of action, the composition has excellent dispersion stability, particularly long-term storage stability. When the composition is allowed to stand at 25°C for 30 days, the fluctuation range (absolute value) of the thixotropy ratio of the composition is preferably 3 or less, and more preferably less than 1.

[0048] The present composition may contain a thixotropy imparting agent, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weather resistance agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a brightening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a viscosity adjusting agent, or a flame retardant, as long as the effects of the present invention are not impaired. The composition may further contain a resin material other than the F polymer, the hydrocarbon-based polymer, and the above-mentioned epoxy resin. Such resin materials may be thermosetting or thermoplastic, may be modified, and may or may not dissolve in the composition. Examples of such resin materials include polyimide resins, polyamic acids which are polyimide precursors, acrylic resins, phenolic resins, liquid crystal polyester resins, polyolefin resins different from the above-mentioned hydrocarbon-based polymers, modified polyphenylene ether resins, polyfunctional cyanate ester resins, polyfunctional maleimide-cyanate ester resins, polyfunctional maleimide resins, vinyl ester resins, urea resins, diallyl phthalate resins, melamine resins, guanamine resins, melamine-urea co-condensation resins, styrene resins, polycarbonate resins, polyarylate resins, polysulfones, polyarylsulfones, aromatic polyamide resins, aromatic polyetheramides, polyphenylene sulfides, polyaryl ether ketones, polyamideimides, and polyphenylene ethers.

[0049] This composition can be prepared by mixing F powder, a hydrocarbon-based polymer, a dispersion medium A, and a dispersion medium B. Examples of mixing methods include a method of adding the above-mentioned components all at once or sequentially and mixing; a method of mixing F powder, dispersion medium A, and dispersion medium B, and then adding a hydrocarbon-based polymer; a method of mixing a hydrocarbon-based polymer, dispersion medium A, and dispersion medium B, and then mixing F powder; a method of previously mixing F powder and dispersion medium A or dispersion medium B, and a method of previously mixing the F powder and dispersion medium A or dispersion medium B, and the hydrocarbon-based polymer and dispersion medium A or dispersion medium B, respectively, and then further mixing the obtained two mixtures. When the present composition contains other materials such as an epoxy resin, an inorganic filler, a surfactant, etc., the other materials may be added at any stage in the production of the present composition, but are preferably added to a mixture containing F powder, a hydrocarbon-based polymer, dispersion medium A, and dispersion medium B. In this case, aggregation of F powder is unlikely to occur when the other materials are mixed, and the present composition is likely to have excellent dispersion stability.

[0050] Examples of mixing methods for preparing the present composition include stirring using a stirring device equipped with uniaxial or multiaxial blades (stirring impellers) such as a propeller blade, turbine blade, paddle blade, or shell-shaped blade, or a Henschel mixer, pressure kneader, Banbury mixer, or planetary mixer; mixing using a disperser that uses media such as a ball mill, attritor, basket mill, sand mill, sand grinder, Dyno Mill (a bead mill using a grinding medium such as glass beads or zirconium oxide beads), Dispermat, SC mill, spike mill, or agitator mill; and mixing using a disperser that does not use media, such as a high-pressure homogenizer such as a Microfluidizer, Nanomizer, or Ultimizer, an ultrasonic homogenizer, a Dissolver, a Disper, or a high-speed impeller disperser.

[0051] A preferred embodiment of the method for producing the present composition includes kneading a mixture containing F powder, a hydrocarbon-based polymer, and dispersion medium A or dispersion medium B to obtain a kneaded mixture, and further mixing the kneaded mixture with dispersion medium A or dispersion medium B. In this embodiment, a kneaded product containing F powder and a high proportion of a hydrocarbon polymer, i.e., a master batch, is obtained, and the master batch is diluted with a dispersion medium to obtain the present composition. In this case, aggregation of F powder during mixing is unlikely to occur, and the present composition can be easily adjusted to the above-mentioned viscosity. As a result, the present dispersion liquid is likely to have excellent dispersion stability and coatability.

[0052] The kneading can be carried out by the above-mentioned mixing method, preferably using a Henschel mixer, a pressure kneader, a Banbury mixer or a planetary mixer, more preferably using a planetary mixer. The planetary mixer has two agitating blades that rotate and revolve around each other, and is structured to agitate and knead the mixture in the agitation tank. Therefore, there is little dead space in the agitation tank where the agitating blades do not reach, and the load on the blades is reduced, allowing the mixture to be kneaded to a high degree. In other words, the F powder can be kneaded while being highly interacted with the hydrocarbon polymer and wetting the F powder with the dispersion medium while suppressing the aggregation of the F powder, and when the mixture is further mixed with the dispersion medium, the present composition having excellent dispersion stability is easily obtained. In addition, the viscosity of the present composition is easy to adjust, and the present composition is easy to form a thick molded product (polymer layer, etc.) with excellent surface smoothness and uniformity.

[0053] The content of the F powder in the mixture is preferably 5 to 60 mass % based on the total mass of the mixture, and the content of the hydrocarbon polymer in the mixture is preferably 10 to 60 mass % based on the total mass of the mixture. The total content of the F powder and the hydrocarbon polymer in the mixture is preferably 40 to 90 mass %, more preferably 50 to 80 mass %, based on the total mass of the mixture. The ratio of the mass of the hydrocarbon polymer to the mass of the F powder in the mixture is preferably 0.5-10, and more preferably 1-5. If the content of F powder, the content of hydrocarbon-based polymer, or the ratio is within the above range, the F powder and the hydrocarbon-based polymer can be mixed while causing a high degree of interaction during kneading of the mixture, and therefore, when the kneaded mixture is further mixed with a dispersion medium, the present composition having excellent dispersion stability is likely to be obtained.

[0054] The kneaded product is a semi-solid or solid kneaded product, and is preferably a kneaded paste or a kneaded powder. Note that the kneaded paste refers to a kneaded product in a state having fluidity and viscosity, and the kneaded powder refers to a kneaded product in a lump-like and clay-like state. The viscosity of the kneaded paste is preferably 800 to 100,000 mPa·s, and more preferably 1,000 to 10,000 mPa·s or more. The content of the dispersion medium A and the dispersion medium B in the kneaded powder is preferably 40% by mass or less, and more preferably 20% by mass or less.

[0055] In this embodiment, when other materials such as an epoxy resin, an inorganic filler, or a surfactant are further contained in the composition, these may be added to the mixture or may be added when the kneaded material and the dispersion medium are mixed. For example, the present composition containing other materials such as an epoxy resin, an inorganic filler, or a surfactant may be obtained by kneading a mixture containing F powder, a hydrocarbon polymer, a dispersion medium A, and a dispersion medium B to obtain a kneaded mixture, and then mixing the kneaded mixture with other materials and the dispersion medium A. In this case, the dispersion stability and long-term storage stability of the present composition are likely to be improved.

[0056] The present composition can also be used as a coating agent capable of forming a resin layer (hereinafter also referred to as "F layer") containing an F polymer and a hydrocarbon polymer on the surface of various substrates when applied thereto. For example, the present composition can be used to easily manufacture sheet materials used for adhesive sheets, coverlay films, etc., with excellent adhesiveness. That is, the method for manufacturing a sheet material of the present invention can be said to be a method in which the present composition is applied to the surface of a sheet substrate to form a liquid coating, the liquid coating is heated, and the liquid dispersion medium is removed from the liquid coating while the F layer is formed.

[0057] When the sheet material in the present invention is an adhesive sheet in which the F layer is used as an adhesive layer between substrates, the sheet base material can be constituted by a release sheet. Furthermore, when the sheet material is a coverlay film that bonds the F layer to a printed wiring board so as to cover the metal wiring, the sheet base material can be made of a heat-resistant resin film. The heat-resistant resin film is a film containing one or more kinds of heat-resistant resins, and may be a single-layer film or a multi-layer film. Examples of the heat-resistant resin include polyimide, polyarylate, polysulfone, polyarylsulfone, aromatic polyamide, aromatic polyetheramide, polyphenylene sulfide, polyaryletherketone, polyamideimide, and liquid crystal polyester.

[0058] The thickness of the F layer is preferably 0.1 to 150 μm. Specifically, when the sheet substrate layer is a metal foil, the thickness of the F layer is preferably 1 to 30 μm. When the sheet substrate layer is a heat-resistant resin film, the thickness of the F layer is preferably 1 to 150 μm, and more preferably 10 to 50 μm. The composition may be applied to only one surface of the sheet substrate layer, or may be applied to both surfaces of the sheet substrate layer. In the former case, a laminate having a sheet substrate layer and an F layer on one surface of the sheet substrate layer is obtained as a sheet material, while in the latter case, a laminate having a sheet substrate layer and an F layer on both surfaces of the sheet substrate layer is obtained as a sheet material. The latter laminate is less likely to warp, and therefore has excellent handling properties during processing. Specific examples of such laminates include metal clad laminates having a metal foil and a polymer layer on at least one surface of the metal foil, and multilayer films having a polyimide film and polymer layers on both surfaces of the polyimide film.

[0059] The metal foil may be a carrier-attached metal foil containing two or more layers of metal foil. The carrier-attached metal foil may be a carrier-attached copper foil consisting of a carrier copper foil (thickness: 10 to 35 μm) and an ultra-thin copper foil (thickness: 2 to 5 μm) laminated on the carrier copper foil via a release layer. By using such a carrier-attached copper foil, it is possible to form a fine pattern by a modified semi-additive (MSAP) process. The release layer is preferably a metal layer containing nickel or chromium, or a multi-layer metal layer in which such metal layers are laminated. A specific example of the metal foil with a carrier is "FUTF-5DAF-2" manufactured by Fukuda Metal Foil & Powder Co., Ltd.

[0060] Here, the outermost surface of the sheet material (the surface opposite to the base layer of layer F) may be further surface-treated in order to further improve its low linear expansion property and adhesiveness. Examples of the surface treatment method include annealing treatment, corona treatment, plasma treatment, ozone treatment, excimer treatment, and silane coupling treatment. The annealing conditions are preferably a temperature of 120 to 180° C., a pressure of 0.005 to 0.015 MPa, and a time of 30 to 120 minutes. Examples of gases used in the plasma treatment include oxygen gas, nitrogen gas, rare gas (argon, etc.), hydrogen gas, ammonia gas, and vinyl acetate. These gases may be used alone or in combination of two or more.

[0061] On the outermost surface of the laminate, another substrate may be further laminated. Other substrates include a heat-resistant resin film, a prepreg which is a precursor of a fiber-reinforced resin plate, a laminate having a heat-resistant resin film layer, and a laminate having a prepreg layer. Note that a prepreg is a sheet-like substrate in which a base material (tow, woven fabric, etc.) of reinforcing fibers (glass fibers, carbon fibers, etc.) is impregnated with a thermosetting resin or a thermoplastic resin. The heat-resistant resin film is a film containing one or more types of heat-resistant resin, and examples of the heat-resistant resin include the resins mentioned above.

[0062] As a method for lamination, a method of hot pressing the laminate and another substrate can be mentioned. When the other substrate is a prepreg, the conditions for the heat press are preferably a temperature of 120 to 400° C., a vacuum atmosphere of 20 kPa or less, and a press pressure of 0.2 to 10 MPa. Since such a laminate has an F layer with excellent electrical properties, it is suitable as a printed circuit board material, specifically, it can be used as a flexible metal-clad laminate or a rigid metal-clad laminate in the manufacture of printed circuit boards, and in particular, it can be used as a flexible metal-clad laminate in the manufacture of flexible printed circuit boards.

[0063] A printed circuit board is obtained by etching the metal foil of a laminate (metal foil with F layer) in which the sheet base layer is a metal foil to form a transmission circuit. Specifically, a printed circuit board can be manufactured by a method of processing a metal foil into a desired transmission circuit by etching the metal foil, or a method of processing a metal foil into a desired transmission circuit by electrolytic plating (semi-additive method (SAP method), MSAP method, etc.). A printed circuit board manufactured from the metal foil with an F layer has a transmission circuit formed from the metal foil and an F layer in this order. Specific examples of the configuration of the printed circuit board include transmission circuit / F layer / prepreg layer and transmission circuit / F layer / prepreg layer / F layer / transmission circuit. In the manufacture of such a printed circuit board, an interlayer insulating film may be formed on a transmission circuit, a solder resist may be laminated on the transmission circuit, or a coverlay film may be laminated on the transmission circuit. These interlayer insulating films, solder resists, and coverlay films may be formed from the present composition.

[0064] The method of applying the composition to the surface of the sheet substrate may be any method that forms a stable liquid coating (wet film) of the composition on the surface of the sheet substrate, and includes coating, droplet ejection, and immersion methods, with the coating method being preferred. The coating method allows the liquid coating to be efficiently formed on the surface of the substrate with simple equipment. Examples of the coating method include spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, and slot die coating.

[0065] During heating, the liquid coating is maintained at the volatilization temperature of the liquid dispersion medium, the liquid coating is dried, and then the dried coating is maintained at a temperature higher than the volatilization temperature of the liquid dispersion medium. In this way, the F layer is formed on the surface of the sheet substrate. The "volatilization temperature of the liquid dispersion medium" is preferably the boiling point of the liquid dispersion medium ±50°C, more preferably a temperature higher than the boiling point of the liquid dispersion medium, and even more preferably a temperature lower than the boiling point of the liquid dispersion medium +50°C. The drying temperature generally refers to the temperature of the drying atmosphere. During drying, the liquid dispersion medium does not necessarily have to be completely evaporated, but it is sufficient to evaporate it to an extent that the layer shape after retention is stable and a free-standing film can be maintained. Specifically, the amount of the liquid dispersion medium to be evaporated is preferably 50% by mass or more of the liquid dispersion medium contained in the composition.

[0066] Drying may be performed in one step at a constant temperature, or in two or more steps at different temperatures. Drying methods include a method using an oven, a method using a ventilated drying furnace, and a method using heat rays such as infrared rays. Drying may be performed under either normal pressure or reduced pressure. The drying atmosphere may be any of an oxidizing gas atmosphere (oxygen gas, etc.), a reducing gas atmosphere (hydrogen gas, etc.), and an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.). The drying temperature is preferably from 50 to 280° C., more preferably from 120 to 260° C. The drying time is preferably from 0.1 to 30 minutes, more preferably from 0.5 to 20 minutes. By drying the liquid coating under the above conditions, the F layer can be suitably solidified while maintaining high productivity.

[0067] The curing method may be a method using an oven, a method using a ventilated drying furnace, a method using heat rays such as infrared rays, or a method using a combination of infrared heating and hot air heating. In order to improve the surface smoothness of the F layer to be formed, the dried coating may be pressed with a heated plate, heated roll, or the like.

[0068] Curing may be performed under normal pressure or reduced pressure. The curing atmosphere may be any of an oxidizing gas atmosphere, a reducing gas atmosphere, and an inert gas atmosphere, but from the viewpoint of suppressing oxidative deterioration of the sheet substrate and the F layer to be formed, a reducing gas atmosphere and an inert gas atmosphere are preferred. The curing temperature is preferably 120°C to 200°C, more preferably 140°C to 180°C, and even more preferably 140°C to 160°C. The curing time is preferably 30 seconds to 30 minutes, and more preferably 1 to 15 minutes. Heating the dried coating under such conditions increases the productivity of the sheet material and also makes it easier to suppress the generation of hydrofluoric acid due to decomposition of the F polymer.

[0069] In conventional liquid compositions containing F powder, dispersants and surfactants are usually added to maintain the dispersion stability, and such dispersants and surfactants remain in the F layer to a considerable extent, which can cause problems in maintaining adhesion to substrates and the like and in handling the sheet material. In this composition, by containing dispersion medium A and dispersion medium B at a specific mass ratio (B / A), the constituent hydrocarbon polymer acts as a dispersant, improving the effects on adhesion and electrical properties caused by the dispersant and surfactant still remaining in the F layer after curing. Furthermore, when the F layer is laminated to other substrates, it can be laminated at a lower temperature with strong adhesion.

[0070] By impregnating a woven fabric with this composition and drying it by heating, an impregnated woven fabric is obtained in which the F polymer is impregnated into the woven fabric. The impregnated woven fabric can also be called a coated woven fabric in which the woven fabric is coated with an F layer (embedded in the F layer). The woven fabric is preferably a glass fiber woven fabric, a carbon fiber woven fabric, an aramid fiber woven fabric, or a metal fiber woven fabric, and more preferably a glass fiber woven fabric or a carbon fiber woven fabric. The woven fabric may be treated with a silane coupling agent from the viewpoint of increasing the adhesion to the F layer. The total content of the F polymer in the impregnated woven fabric is preferably 30 to 80% by mass. Methods for impregnating the woven fabric with the present composition include a method of immersing the woven fabric in the present composition and a method of applying the present composition to the woven fabric.

[0071] When drying the woven fabric, the F polymer may be calcined. The F polymer may be calcined by passing the woven fabric through a forced-air drying oven in an atmosphere of 300 to 400°C. The drying of the woven fabric and the calcination of the polymer may be carried out in one step. The impregnated woven fabric has excellent properties such as high adhesion (bonding) between the F layer and the woven fabric, high surface smoothness, and little distortion. By thermocompression bonding such an impregnated woven fabric and a metal foil, a metal clad laminate having high peel strength and resistance to warping can be obtained, which can be suitably used as a material for printed circuit boards.

[0072] The liquid composition, the method for producing the liquid composition, and the method for producing the sheet material of the present invention have been described above, but the present invention is not limited to the configurations of the above-mentioned embodiments. For example, in the liquid composition of the present invention, any other components may be added to the components of the above-mentioned embodiments, or any other components that exhibit similar functions may be substituted. Furthermore, the method for producing a liquid composition and the method for producing a sheet material of the present invention may have any other steps in addition to the configurations of the above embodiments, or may be replaced with any steps that produce a similar effect. EXAMPLES

[0073] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Details of each component are shown below. [F Powder] F Powder 1: Powder made of a polymer (melting temperature 300°C) having an acid anhydride group, containing 97.9 mol% of TFE units, 0.1 mol% of NAH units, and 2.0 mol% of PPVE units, in that order (average particle size 2 μm, bulk density 0.18 g / m 2 ) F Powder-2: Powder made of a polymer (melting temperature 305°C) with no functional groups, containing 97.5 mol% TFE units and 2.5 mol% NAH units, in that order (average particle size 2 μm, bulk density 0.19 g / m 2 ) F Powder 3: Powder made of PTFE with a number average molecular weight of 20,000 (average particle size 0.3 μm, bulk density 0.2 g / m 2 ) [Hydrocarbon polymers] Polymer 1: Tuftec MP-10 (Asahi Kasei Corporation, amino group-modified SEBS) Polymer 2: Tuftec M1913 (Asahi Kasei Corporation, acid-modified SEBS) Polymer 3: Tuftec H1041X (manufactured by Asahi Kasei Corporation, unmodified SEBS) [solvent] Tol: Toluene (a non-polar liquid dispersion medium with a Rohrschneider polarity parameter of 2.4) MEK: Methyl ethyl ketone (a polar liquid dispersion medium with a Rohrschneider polarity parameter of 4.7) [Epoxy resin] Epoxy resin 1: EPICLON HP-6000 (DIC Corporation, naphthalene-type epoxy resin) [Filler] Filler 1: Silica filler (average particle size 0.4 μm) [Surfactants] Surfactant 1: CH 2 =C(CH 3 )C(O)OCH 2 CH 2 (CF 2 ) 6 F and CH 2 =C(CH 3 )C(O)(OCH 2 CH 2 ) 23 A nonionic polymer that is a copolymer with OH and has a fluorine content of 35% by mass.

[0074] [Example 1-1] Production and evaluation of liquid composition (1) First, F powder 1, Tol, and MEK were put into a pot, and zirconia balls were put in. Then, the pot was rolled at 150 rpm for 1 hour to prepare a composition. Furthermore, polymer 1 was put into the pot, and the pot was rolled at 150 rpm for 2 hours to prepare a composition. Furthermore, epoxy resin 1 and filler 1 were put into the pot, and the mixture was stirred for 30 seconds at a rotation speed of 20,000 rpm with a homodisper, and liquid composition 1 (viscosity: 400 mPa s, mass ratio of polar liquid dispersion medium content to non-polar liquid dispersion medium content: 0.33) containing F powder 1 (5 parts by mass), polymer 1 (15 parts by mass), epoxy resin 1 (1 part by mass), filler 1 (2 parts by mass), Tol (58 parts by mass), and MEK (19 parts by mass) was obtained. (2) Regarding dispersion stability, the state of the obtained Liquid Composition 1 immediately after preparation and the state after storage in a container at 25°C for 3 hours were visually confirmed, and the coagulation and sedimentation properties were evaluated according to the following criteria. <Evaluation criteria for cohesion> 〇: Immediately after preparation and after storage, there was little foaming, no agglomerates were observed, and the mixture was uniformly dispersed. △: Some aggregates were observed both immediately after preparation and after storage. ×: Many aggregates observed and not uniformly dispersed <Evaluation criteria for sedimentation> ○: No sediment was observed immediately after preparation and after storage. △: Some aggregates formed after storage and adhered to the walls of the container, but were dispersed evenly when lightly stirred. ×: A large amount of aggregates precipitated after storage. They were uniformly redispersed when stirred with shear.

[0075] [Example 1-2 to Example 1-9] Liquid compositions 2 to 9 were obtained in the same manner as in Example 1-1, except that the type and amount of each component and the mass ratio of the polar liquid dispersion medium content to the non-polar liquid dispersion medium content (ratio of polar liquid dispersion medium to non-polar liquid dispersion medium) were changed as shown in Table 1. [Example 1-10] First, F powder 1, polymer 1, Tol, and MEK were put into a pot and mixed to prepare a mixture. This mixture was kneaded in a planetary mixer and then removed to obtain kneaded paste 1 containing F powder 1 (5 parts by mass), polymer 1 (15 parts by mass), Tol (10 parts by mass), and MEK (19 parts by mass). The viscosity of kneaded paste 1 was 27,000 mPa s. A mixture containing epoxy resin 1, filler 1, and Tol was added to the kneaded paste 1 in several batches while stirring with a planetary centrifugal mixer at 2000 rpm while degassing, to obtain a liquid composition 10 (viscosity: 300 mPa s, mass ratio of polar liquid dispersion medium content to non-polar liquid dispersion medium content: 0.33) containing F powder 1 (5 parts by mass), polymer 1 (15 parts by mass), epoxy resin 1 (1 part by mass), filler 1 (2 parts by mass), Tol (58 parts by mass), and MEK (19 parts by mass). In addition, Liquid Composition 1 and Liquid Composition 10 were stored in a container at 25°C for 30 days, and the range of fluctuation in the thixotropic ratio before and after storage was measured. As a result, the range of fluctuation (absolute value) of the thixotropic ratio of Liquid Composition 1 was 1 or more and 3 or less, and the range of fluctuation of Liquid Composition 10 was less than 1. The results of evaluation of the coagulation property and sedimentation property of the obtained liquid composition are shown in Table 1.

[0076] [Table 1]

[0077] [Example 2-1] Manufacturing and evaluation of adhesive sheets The obtained liquid composition 1 was applied to a release film by a die coating method to form a liquid coating. Then, this liquid coating was passed through a drying oven at 120°C for 5 minutes, heated and dried to obtain a dry coating. The dry coating was then heated and cured in a far-infrared oven at 180°C for 10 minutes to obtain a laminate 1 in which an F layer having a thickness of 50 μm was formed on the surface of the release film 1, and the surface smoothness and dielectric loss tangent were evaluated as follows. The results are shown in Table 2. <Surface smoothness evaluation and evaluation criteria> The surface smoothness of the F layer of the laminate 1 was visually inspected and evaluated according to the following criteria. ◯: The entire surface of the F layer is smooth. △: The edge of layer F is raised and the center is depressed. ×: The edges of the F layer are raised and the center is depressed, and irregularities due to loss of polymer or inorganic filler are also observed. <Dielectric tangent> A sample with a length of 10 cm and a width of 5 cm was cut out from the obtained laminate 1, and the release film was removed to obtain a polymer layer alone. The dielectric loss tangent (measurement frequency: 10 GHz) of the polymer layer was measured under an environment of 23°C ± 2°C and 50 ± 5% RH by the SPDR (split post dielectric resonance) method.

[0078] [Example 2-2 to Example 2-10] Laminates 2 to 10 were obtained in the same manner as in Example 2-1, except that Liquid Compositions 2 to 10 were used, respectively. The surface smoothness of each laminate was evaluated, and the dielectric loss tangent was further evaluated for Laminates 1 to 4, 8, 9, and 10, which had high surface smoothness. The results are shown in Table 2.

[0079] [Table 2] [Industrial Applicability]

[0080] The liquid composition of the present invention has excellent dispersion stability and can be easily processed into films, fiber-reinforced films, prepregs, and metal laminates (metal foils coated with resin). The processed articles obtained can be used as materials for antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, sliding bearings, etc.

Claims

1. A powder of a tetrafluoroethylene-based polymer having a volume-based cumulative 50% diameter of 0.01 μm or more and 20 μm or less, a styrene-based polymer, a non-polar liquid dispersion medium, and a polar liquid dispersion medium, wherein the mass ratio of the content of the styrene-based polymer to the content of the powder is 0.5 to 10, and the mass ratio of the content of the polar liquid dispersion medium to the content of the non-polar liquid dispersion medium is 0.1 or more and 1 or less, the non-polar liquid dispersion medium is benzene, toluene, xylene, ethylbenzene, styrene, cumene, mesitylene (1,3,5-trimethylbenzene), cymene, diethylbenzene or naphthalene; The polar liquid dispersion medium is acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, or cycloheptanone; Liquid composition.

2. The liquid composition of claim 1, wherein the styrene-based polymer is a styrene-conjugated diene block copolymer.

3. The liquid composition according to claim 1 or 2, wherein the styrene-based polymer has a polar group.

4. The liquid composition according to any one of claims 1 to 3, wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing a unit based on perfluoro(alkyl vinyl ether) or a unit based on hexafluoropropene, or a polytetrafluoroethylene having a number average molecular weight of 200,000 or less.

5. The liquid composition according to any one of claims 1 to 4, wherein the content of the tetrafluoroethylene polymer powder is 5 mass% or more based on the total mass of the liquid composition.

6. The liquid composition according to any one of claims 1 to 5, which does not contain any fluorine-containing compound other than the tetrafluoroethylene-based polymer.

7. The method for producing a liquid composition according to any one of claims 1 to 6, further comprising kneading a composition containing the tetrafluoroethylene-based polymer powder, the styrene-based polymer, and the non-polar liquid dispersion medium or the polar liquid dispersion medium to obtain a kneaded mixture, and mixing the kneaded mixture with the non-polar liquid dispersion medium or the polar liquid dispersion medium to obtain the liquid composition.

8. The method according to claim 7 , wherein the kneaded product is a kneaded paste or a kneaded powder.

9. A sheet material formed from the liquid composition according to any one of claims 1 to 6.

10. 10. The sheet material according to claim 9, which is an adhesive sheet used as an adhesive layer between substrates.

11. 10. The sheet material according to claim 9, which is a coverlay film that is adhered to a printed wiring board so as to cover metal wiring.

Citation Information

Patent Citations

  • Resin composition, insulating film using the same, and semiconductor device

    JP2016089137A

  • Fluororesin nonaqueous dispersion, fluororesin-containing thermosetting resin composition prepared therewith and cured product thereof

    JP2017222761A

  • Fluororesin nonaqueous dispersion, fluororesin-containing thermosetting resin composition prepared therewith and cured product thereof

    JP2017222762A

  • Resin composition

    JP2019035059A

  • Thermosetting resin composition, dry film, cured product, and electronic component

    JP2019167426A